Biogenic nanomaterials from photosynthetic microorganisms. (June 2015) - Jeffryes, Clayton; Agathos, Spiros N; Rorrer, Gregory
Graphical abstract: Highlights: Algal cell cultures can produce nanostructured biopolymers. Au 0 and Ag 0 nanoparticles can be continually produced by algae. Diatom biosilica can be functionalized in vitro and in vivo . Optoelectronic materials from algal cell culture can be used as biosensors. Numerical models have been recently developed to describe biosilica formation. Abstract : The use of algal cell cultures represents a sustainable and environmentally friendly platform for the biogenic production of nanobiomaterials and biocatalysts. For example, advances in the production of biogeneic nanomaterials from algal cell cultures, such as crystalline β-chitin nanofibrils and gold and silver nanoparticles, could enable the 'green' production of biomaterials such as tissue-engineering scaffolds or drug carriers, supercapacitors and optoelectric materials. The in vivo functionalization, as well as newly demonstrated methods of production and modification, of biogenic diatom biosilica have led to the development of organic–inorganic hybrid catalytic systems as well as new biomaterials for drug delivery, biosensors and heavy-metal adsorbents.